2004
DOI: 10.1161/01.str.0000114877.58809.3d
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Perfusion Imaging With Contrast-Enhanced Ultrasound in Acute Ischemic Stroke

Abstract: Background and Purpose-Color-coded perfusion maps can be calculated from ultrasound harmonic gray-scale imaging data after ultrasound contrast agent bolus injection to analyze brain tissue perfusion. First reports indicate that this method can display cerebral perfusion deficits in acute ischemic stroke. We performed a prospective patient study to evaluate this approach. Methods-Thirty consecutive patients suffering from acute middle cerebral artery infarction who presented to our department within 12 hours af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 15 publications
1
58
0
3
Order By: Relevance
“…Many studies have demonstrated the value of UPI for the depiction of blood flow in the microcirculation of the brain in healthy animals [82,83] and humans [84]. Furthermore, there is mounting evidence that echo contrast harmonic imaging can be used to visualize perfusion deficits in patients with acute stroke, although the studies have used different harmonic imaging modalities [11, 85, 86]. …”
Section: Us Perfusion Imaging In Cerebral Ischemiamentioning
confidence: 99%
“…Many studies have demonstrated the value of UPI for the depiction of blood flow in the microcirculation of the brain in healthy animals [82,83] and humans [84]. Furthermore, there is mounting evidence that echo contrast harmonic imaging can be used to visualize perfusion deficits in patients with acute stroke, although the studies have used different harmonic imaging modalities [11, 85, 86]. …”
Section: Us Perfusion Imaging In Cerebral Ischemiamentioning
confidence: 99%
“…5) such as the time to peak intensity (TPI), the peak intensity (PI), the mean transit time, the peak width (full width at 90% of the maximum intensity and full width at half the maximum intensity), the area under the curve, the positive gradient (defined as PI/TPI), and the peak signal increase. These parameters can then be displayed as parametric images [52]. …”
Section: Examination Of the Microcirculation – Brain Perfusion Imagingmentioning
confidence: 99%
“…Several studies have shown that such parameters may be suitable for assessment of the perfusion state, particularly the analysis of local time-intensity curves in prespecified ROI [37] or the visual interpretation of parametric images [52,53,54,55,56]. MRI and PET studies in acute stroke patients have demonstrated the diagnostic value of TPIs maps for differentiation between unaffected parenchyma, penumbra, and ischemic core area [57].…”
Section: Examination Of the Microcirculation – Brain Perfusion Imagingmentioning
confidence: 99%
“…2) such as time-to-peak intensity (TPI), peak intensity (PI), mean transit time, peak width (full width at 90% of the maximum intensity and full width at half the maximum intensity), area under the curve, positive gradient (defined as peak intensity/TPI), and peak signal increase. These parameters can then be displayed as parametric images [15]. …”
Section: Bolus Kineticsmentioning
confidence: 99%
“…Several studies have shown that such parameters may be suitable for assessment of the perfusion state, particularly the analysis of local time-intensity curves in prespecified regions of interest [5] or the visual interpretation of parametric images [15,16,17,18,19]. MRI and PET studies in acute stroke patients have demonstrated the diagnostic value of TPI maps for differentiation between unaffected parenchyma, penumbra, and ischemic core area [20].…”
Section: Bolus Kineticsmentioning
confidence: 99%